2020
DOI: 10.1101/2020.11.18.20232272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethical and psychosocial considerations for hospital personnel in the Covid-19 crisis: Moral injury and resilience

Abstract: This study aims at investigating the nature of resilience and stress experience of health care workers during the COVID-19 pandemic. Thirteen healthcare workers from Italian and Austrian hospitals specifically dealing with COVID-19 patients during the first phase of the pandemic were interviewed. Data was analysed using grounded theory methodology. Psychosocial effects on stress experience, stressors and resilience factors were identified. We generated three hypotheses. Hypothesis one is that moral distress an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 43 publications
(29 reference statements)
2
46
0
Order By: Relevance
“…28 Once the crisis is over, a major task should therefore be after care, addressing moral injury in HCWs and rebuilding trust in the system. 29,30 We also found that some nurses who have no professional infectious disease background or training were recruited from other wards to remedy staff shortages. Redeployment of staff without specific training may lead to absenteeism, especially once the crisis is over.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…28 Once the crisis is over, a major task should therefore be after care, addressing moral injury in HCWs and rebuilding trust in the system. 29,30 We also found that some nurses who have no professional infectious disease background or training were recruited from other wards to remedy staff shortages. Redeployment of staff without specific training may lead to absenteeism, especially once the crisis is over.…”
Section: Discussionmentioning
confidence: 92%
“…21 Other studies found that HCWs experience moral injury as a consequence of their commitment. 28,29 Insufficient protection, as well as other factors such as (lack of) actions that violate one's ethical principles (e.g. not being able to provide good quality care to patients due to being overworked), lead to negative selfperception and distrust in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Social pressures: negative societal stigma, discomfort with the environment, the presence of strangers, changes in relationships with patients and relatives, decreased closeness to other relatives, fear of being stigmatized by others, and injustice. Alizadeh et al, 2020;Kackin et al, 2020;Sun et al, 2020;Kreh et al, 2021. Uncertainty: Changes in work patterns, heavy work and difficulties in communicating with patients, new roles or tasks and broken routines, and uncertainty about future conditions. Cui et al, 2020;Kackin et al, 2020;Kreh et al, 2021. Study Zhang et al (2020) stated that nurses who work to treat COVID-19 patients undergo a process of change at work into three stages, namely the initial stage (ambivalence), the middle stage (emotional exhaustion), and the next stage (energy renewal).…”
Section: Forms Of Nurse Psychosocial Response Patient's Care Of Covid-19mentioning
confidence: 99%
“…Alizadeh et al, 2020;Kackin et al, 2020;Sun et al, 2020;Kreh et al, 2021. Uncertainty: Changes in work patterns, heavy work and difficulties in communicating with patients, new roles or tasks and broken routines, and uncertainty about future conditions. Cui et al, 2020;Kackin et al, 2020;Kreh et al, 2021. Study Zhang et al (2020) stated that nurses who work to treat COVID-19 patients undergo a process of change at work into three stages, namely the initial stage (ambivalence), the middle stage (emotional exhaustion), and the next stage (energy renewal). At each stage, nurses have different psychological characteristics.…”
Section: Forms Of Nurse Psychosocial Response Patient's Care Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation